2019
DOI: 10.1523/jneurosci.0355-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neural Variability Is Quenched by Attention

Abstract: Attention can be subdivided into several components, including alertness and spatial attention. It is believed that the behavioral benefits of attention, such as increased accuracy and faster reaction times, are generated by an increase in neural activity and a decrease in neural variability, which enhance the signal-to-noise ratio of task-relevant neural populations. However, empirical evidence regarding attention-related changes in neural variability in humans is extremely rare. Here we used EEG to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 58 publications
2
27
2
Order By: Relevance
“…Several studies have found that spatial attention lowers neural spiking variability [40,57,[59][60][61]. Here, we have shown that arousal lowers neural response variability as well, albeit when measured with hemodynamics rather than spikes.…”
Section: Relationship To Previous Studiessupporting
confidence: 52%
“…Several studies have found that spatial attention lowers neural spiking variability [40,57,[59][60][61]. Here, we have shown that arousal lowers neural response variability as well, albeit when measured with hemodynamics rather than spikes.…”
Section: Relationship To Previous Studiessupporting
confidence: 52%
“…Interestingly, this effect was largely constant throughout the post-stimulus period, rather than peaking and decreasing as with the power-based results. In contradiction to this finding, however, we observed (as seen in previous studies 59,66,67 ) a reduction in TTV, occurring from 200 ms to 700 ms post-stimulus (p = 0.002), as well as an early increase in TTV (p = 0.006). This reduction in TTV, interpreted traditionally as in He (2013), should imply a negative interaction, in direct conflict with the results observed using the method of pseudotrials.…”
Section: Spontaneous-evoked Interaction In the Time Domain -Conflict contrasting
confidence: 99%
“…This trial-by-trial variability is relatively large before stimulus presentation, and strongly reduced (quenched) approximately 200 ms after stimulus presentation 7 . Neural variability quenching is a robust phenomenon that has been reported in intracellular membrane potential recordings in cats, extracellular recordings of spiking activity in monkeys 7,8 , and in human electroencephalography (EEG) 912 , electrocorticography (ECOG) 13 , magnetoencephalography (MEG) 11 , and functional magnetic resonance imaging (fMRI) recordings 14,15 . Furthermore, the phenomenon was reported during both awake and anaesthetized states, and in several cortical areas 7,15 using a variety of sensory stimuli 7,10 .…”
Section: Introductionmentioning
confidence: 99%